Experimental and numerical analyses of quenching performance of hot stamping blanks by two-phase refrigerant cooling using R1234yf. (July 2021) - Yun, Sungho; Hong, Seong Ho; Song, Kang Sub; Kwon, Junho; Kim, Yongchan
Highlights: Two-phase refrigerant cooling for hot stamping is proposed for improved quenching. Experimental and numerical studies on quenching performances are conducted. R1234yf cooling realizes a better cooling performance and higher blank quality. R1234yf cooling achieves a 9.5–15.3% greater daily production than water cooling. ABSTRACT: This study aims to investigate the quenching performance of hot stamping blanks by two-phase refrigerant and conventional single-phase cooling. A low-global-warming potential refrigerant, R1234yf, is used as the working fluid for the two-phase refrigerant cooling. The quenching performance of the water and R1234yf cooling methods is evaluated experimentally and via simulations using a three-dimensional transient thermo-fluid model. The R1234yf cooling method presents a higher cooling capacity and energy efficiency than the water cooling method owing to the effective evaporative heat transfer characteristics of the former. Under the same mass flow rate conditions, the blank hardness and its standard deviation achieved by the R1234yf cooling method are 7.3–31.5 HV higher and 13.1–54.3% lower than those by the water cooling method, respectively. Furthermore, the R1234yf cooling method decreases the hotspot area in the internal lower die and realizes a more uniform temperature distribution compared to water cooling. In addition, the daily production by the R1234yf cooling method is 9.5 − 15.3% higher than that by the water cooling method owing to the shorter approach time to the martensite finish temperature in the former. Accordingly, owing to its higher blank quality and productivity, the R1234yf cooling method has a superior quenching performance than water cooling during the hot stamping process.